Optimization of microtubule affinity regulating kinase (MARK) inhibitors with improved physical properties. Issue 17 (1st September 2016) - Sloman, David L.; Noucti, Njamkou; Altman, Michael D.; Chen, Dapeng; Mislak, Andrea C.; Szewczak, Alexander; Hayashi, Mansuo; Warren, Lee; Dellovade, Tammy; Wu, Zhenhua; Marcus, Jacob; Walker, Deborah; et al.
Graphical abstract: Abstract: Inhibition of microtubule affinity regulating kinase (MARK) represents a potentially attractive means of arresting neurofibrillary tangle pathology in Alzheimer's disease. This manuscript outlines efforts to optimize a pyrazolopyrimidine series of MARK inhibitors by focusing on improvements in potency, physical properties and attributes amenable to CNS penetration. A unique cylcyclohexyldiamine scaffold was identified that led to remarkable improvements in potency, opening up opportunities to reduce MW, Pgp efflux and improve pharmacokinetic properties while also conferring improved solubility.